The role of Sulh towards the process of reducing the rate of divorce in the Kadhis’courts in Zanzibar: Following the Malaysian model - Arifin, Mahamad; Ibrahim, Norliah; Talib, Mwinyi (INSI Publications, 2012)
It is an undeniable fact that the issue of divorce is very crucial in Zanzibar as its rate increases day after day. However, a significant number of spouses in the islands want chiefly to air their difficulties before some authoritative body which would identify the basic problems for all spouses concerned and offer advice on how they could be solved short of termination of their marriage. Despite the fact that divorce is a common practice in Zanzibar, there is certain number of marital problems where the spouses are willing to give their marriage another chance by relying greatly on Sulh but failure of having this mechanism in the Kadhis’ Courts results in many marital conflicts ending with the dissolution. Therefore, this paper at the outset seeks to examine the rate of divorce in Zanzibar. This is made purposely in order to get the clear picture concerning the aspect of divorce in Zanzibar. The second part of the paper will focus on observing the current procedures applied in solving the marital disputes in Zanzibar. The last part of the paper will focus on showing the importance of introducing Sulh process before the Kadhis’ Courts in Zanzibar as a mechanism to reduce the rate of divorce. Thus, in order for the Sulh process to be effective, this paper seeks to show the relevancy of the Malaysian model for the intended changes in Kadhis’ Courts in Zanzibar.